Optimization of a primary gravity separation treatment for vegetable oil refinery wastewaters - Ariana M. A. Pintor (2014)
Vegetable oil refinery wastewaters (VORW) are loaded with organic and oily matter, and cannot be decontaminated by conventional treatment methods. Pretreatment methods with the objective of decreasing oil and grease (O&G) and chemical oxygen demand (COD) content either generate hazardous byproducts or may be too costly. In this paper, it is demonstrated that gravity separation is appropriate as a low-cost primary treatment for VORW. The kinetics of the oil/water separation process was studied by measuring O&G and also COD concentrations over time in the aqueous bottom phase of two types of VORW left in quiescence. Removals after 24 h exceeded 90 % for O&G and varied between 58 and 90 % for COD. An empirical model was fitted to the experimental data with good correlation (r (2) > 0.975 for all datasets). Newton's laws and Stokes' law were used to predict the behavior of oil particles according to size. 3D surface plots were drawn to visualize how the time of removal of an oil droplet changed depending on its velocity, diameter and initial height in the separation column. A retention time of 30 min was selected as the optimum treatment in the separating column, thereby combining the advantages of short treatment time with high O&G removal (over 80 % in both wastewaters).